Influence of fertilizer combination, planting density and varieties on cassava (manihot esculenta crantz) stem yield - Mashuubu, Y.Y. (2023)
Cassava (Manihot esculenta Crantz), is the second staple after maize which contributes to food, feed and cash crop in Tanzania. The crop is a drought tolerant and can yield better than other crops in areas with erratic rains and in years with low total and poor rainfall distribution. However, its root yield is low due to the use of stem cuttings from land races, improper planting densities and declining soil fertility. The study was conducted to determine the effects of fertilizer combinations, planting density and variety on growth and stem yields of cassava. To evaluate the effect of fertilizing cassava plants on sprouting, growth and vigor of a subsequent crop. To assess the economic feasibility of different fertilizer combinations, improved varieties and planting density on cassava stem cuttings. One field trial and one pot experiment was conducted at TARI Ilonga, Kilosa District Tanzania. The field experiment was arranged in a split split plot in a randomized complete block design (RCBD) with variety, planting density and levels of fertilizer combinations as main, sub and sub sub factors, respectively. Cassava varieties used were Kiroba, Chereko and Mkuranga 1, planting densities of 10 000, 13 000 and 20 000 plants ha-1 and 10 fertilizer rates. Data collected were soil physico-chemical characteristics of the site, total plant height, stem height, stem diameter, number of cuttings ha-1 and number of nodes stem cutting-1. The plant data were subjected to analysis of variance (ANOVA) and means were compared using Tukey‟s honestly significance (p<0.05). Interactions of significant factors was also performed using Tukey‟s honestly significance (p<0.05). Application of N at 150N-0P-0K kg N ha-1 produced significantly higher total plant height and stem height, while planting density of 20 000 plants ha-1 and Kiroba variety produced significantly higher numbers of stem cuttings ha-1.